Carbonylation of alkynes, alkenes and alcohols using metal complex catalysts - Sarkar, B. R.; Chaudhari, Raghunath V. (Catalysis Surveys from Asia, 2005)
Carbonylation of olefins, alcohols and halides using homogeneous as well as heterogeneous catalysts has been discussed. Highlights of contributions on the activity, selectivity and stability of catalysts for carbonylation reactions are discussed. Kinetics and mechanism including characterization of the intermediate catalytic species has also been reviewed. The performance of anchored Pd complexes on mesoporous supports (MCM-41 and MCM-48), water soluble Pd complexes and supported Pd catalysts in carbonylation of aryl alcohols and olefins has been discussed in the context of catalyst-product separation. Some aspects of kinetic modelling and reaction engineering of these multiphase catalytic reactions have also been reviewed.
Keywords: Carbonylation; catalysis; Heterogenization; homogeneous; Palladium

New synthetic approach to a [1.1.6] metapara cyclophane derivative via Suzuki-Miyaura cross-coupling and ring-closing metathesis - Kotha, S; Mandal, K; Arora, KK; Pedireddi, R (Advanced Synthesis & Catalysis, 2005)
The synthesis of a [1.1.6] metapara cyclophane derivative, 1,5(1,4),3(1,3)-tribenzenacycloun-decaphan-8-ene-6,11-dione, has been achieved via the Suzuki-Miyaura cross-coupling of alpha,alpha'-dibromo-m-xylene with an arylboronic acid derivative followed by an allylation and ring-closing metathesis reaction sequence.
Keywords: Cyclophanes; olefin metathesis; Palladium; ruthenium; Suzuki-Miyaura cross-coupling

Palladium mediated cycloisomerization of sugar alkynols: synthesis of cyclic enol-ethers and spiroketals - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
Functionalized bicyclic enol-ethers and spiroketals are prepared by Pd catalyzed cycloisomerization of 3-C-alkynylfuranosyl derivatives. Cycloisomerization of differently substituted alkyne derivatives revealed a preference for 6-endo-dig cyclization over 5-exo-dig if the substituent is not sufficiently electron withdrawing. The scope of these cycloisomerizations has been further extended by integrating with conjugate addition. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: c-alkynylfuranose; cycloisomerization; enol-ether; Palladium; Spiroketal

Rate enhancement in palladium catalyzed Heck reactions by Lewis acid promoters - Sud, Abhishek; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Catalysis Communications, 2007)
Significant enhancement in the rate of Heck reactions has been achieved when catalytic amounts of Lewis acid (like FeCl(3)) promoters in the presence of trace amounts of water (> 2000 ppm) are used along with Pd complex catalysts. Experiments with different aryl halides, bases as well as olefins have been carried out to demonstrate the role of Lewis acid promoters. The increase in the reaction rates is due to the weakening of Ar-X bond by the Lewis acid in the manner similar to Friedel-Crafts reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Heck reaction; Lewis acid; Palladium; Promoters

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Influence of electronic factors on palladium-mediated cycloisomerization: a systematic investigation of competitive 5-exo-dig versus 6-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Mallik, Rosy; Gonnade, Rajesh G. (Tetrahedron, 2008)
Pd-mediated cycloisomerization of 3-C-alkynyl-allo- and ribofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity in ring closure reaction. The reactions in general are influenced by the electronic nature of the substituent on the alkyne unit. A preference for endo-dig cyclization over exo-dig is noted, if the alkynyl substituent is not sufficiently electron withdrawing, (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: C-alkynyl furanose; cycloisomerization; enol ether; Palladium; Spiroketal

Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol

Kinetic evidence for the influence of subsurface oxygen on palladium surfaces towards CO oxidation at high temperatures - Gopinath, Chinnakonda S.; Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan (Chemistry-an Asian Journal, 2009)
Transient state kinetics of the catalytic oxidation of CO with 0, on Pd-surfaces has been measured under isothermal conditions by using a molecular beam approach. Systematic studies were carried out as a function of reaction temperature and CO+O(2) composition. With sufficient kinetic evidence, we have demonstrated the positive influence of subsurface oxygen towards CO-adsorption and oxidation to CO, at high temperatures (600-900 K) on Pd-surfaces, and the likely electronic nature of the surface changes with oxygen in the subsurface. These studies also provide a direct proof for CO-adsorption with a significantly reactive sticking coefficient at high temperatures on Pd-surfaces exhibiting a significant subsurface O-coverage.
Keywords: Adsorption; kinetics; Oxidation; Palladium; surface analysis

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Pd-catalyzed one-pot chemoselective hydrogenation protocol for the preparation of carboxamides directly from azides - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Thierry, Josiane; Dodd, Robert H. (Tetrahedron Letters, 2010)
Carboxamides were obtained efficiently in high yields from azides on reaction with the corresponding pre-formed activated carboxylic acids in a single-step reductive transformation using hydrogen atmosphere (balloon) under Pd/BaSO(4) or Pd/CaCO(3) catalysis. The method is highly chemoselective and compatible with extremely labile functional groups such as benzyl carbamates, benzyl ethers, benzyl esters, and olefins. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Azide; Carboxamide; Catalytic hydrogenation; Chemoselective; Palladium; Succinimide ester

Elaboration of the ether cleaving ability and selectivity of the classical pearlman's catalyst [Pd(OH)(2)/C]: concise synthesis of a precursor for a myo-inositol pyrophosphate - Mart, Alson; Shashidhar, Mysore S. (Tetrahedron, 2012)
The cleavage of propargyl, allyl, benzyl, and PMB ethers by Pd(OH)(2)/C can be tuned in that order, by varying the reaction conditions. Other moieties such as C-C double bonds, esters, trityl ether, p-bromo and p-nitrobenzyl ethers are stable to these reaction conditions. Cleavage of allyl ethers can be made catalytic by using 1:1 mixture of Pd(OH)(2)/C and Pd/C. The synthetic potential of the selective ether cleaving ability of Pd(OH)(2)/C, essentially under neutral conditions, has been demonstrated by an efficient synthesis of a precursor for the preparation of an inositol pyrophosphate derivative. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Ether cleavage; Inositol; Palladium; Protecting group

Influence of Pd-loading on gas sensing characteristics of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Nanocrystalline pristine and 0.5, 1.5 and 3.0 wt% Pd loaded SnO2 were synthesized by a facile co-precipitation route. These powders were screen-printed on alumina substrates to form thick films to investigate their gas sensing properties. The crystal structure and morphology of different samples were characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The 3.0 wt% Pd:SnO2 showed response of 85% toward 100 ppm of LPG at operating temperature of 250 degrees C with fast response (8 s) and quick recovery time (24 s). The high response toward LPG on Pd loading can be attributed to lowering of crystallite size (9 nm) as well as the role of Pd particles in exhibiting spill-over mechanism on the SnO2 surface. Also selectivity of 3.0 wt% Pd:SnO2 toward LPG was confirmed by measuring its response to other reducing gases like acetone (CH3COCH3), ethanol (C2H5OH) and ammonia (NH3) at optimum operating temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: LPG sensor; Palladium; SnO2; Thick film

Pd-catalyzed selective hydrosilylation of aryl ketones and aldehydes - Chouthaiwale, Pandurang V.; Rawat, Varun; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Pd salts in combination with triethylsilane as hydride source and DMF as solvent has been found to be excellent catalytic combination that selectively reduces aryl ketones and aldehydes under mild conditions to afford triethylsilyloxy compounds in excellent yields. Product selectivity to the respective benzyl alcohols can however be achieved when the reaction was performed in DMF/H2O (4:1) as solvent system. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Hydrosilylation; Ketones; Palladium; Triethylsilane

Pd ultra-small clusters as precursors for silica-encapsulated Pd nanoreactors: highly sinter-resistant catalysts - Samanta, Anupam; Devi, R. Nandini (Chemcatchem, 2013)
Sintering and consequent deactivation in supported metal catalysts is a severe problem encountered in heterogeneous catalysis. This problem can be addressed by encapsulating active metal nanoparticles within inert oxides such as silica, provided the oxide shell is porous to enable access of reactant molecules to the nanoparticle surface to facilitate catalysis. We report the synthesis of highly sinter-resistant silica-encapsulated Pd catalysts with nanoparticle sizes stabilized at (3.4 +/- 0.6)nm at high temperatures of approximately 750 degrees C. The synthesis was achieved by utilizing thiol-protected ultra-small clusters of Pd as precursors for silica encapsulation. The ultra-small clusters were synthesized by using propyl ammonium functionalised thiols making them water-dispersible and amenable for silica encapsulation. Abundance of organics also aided in creating porosity subsequent to calcination at high temperatures.
Keywords: cluster compounds; Encapsulation; nanoreactors; Palladium; silicates

Target cum flexibility: simple access to benzofuran conjugated sugar and nucleoside derivatives - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, C. V. (Tetrahedron Letters, 2013)
The [Pd]-catalyzed domino process comprising of the coupling of alkynes and o-iodophenol and the subsequent cyclization leading to benzofurans has been successfully applied on the sugar and nucleoside derived alkynes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzofuran; carbohydrates; cyclization; Nucleoside; Palladium

Direct allylation of in situ generated aldehyde acyl anions by synergistic NHC and palladium catalysis - Ahire, Milind M.; Mhaske, Santosh B. (Angewandte Chemie-International Edition, 2014)
The direct regioselective allylation of in situ generated aldehyde acyl anions has been achieved by synergistic NHC and Pd catalysis. It provides an efficient access to valuable beta,gamma-unsaturated ketones under mild reaction conditions starting from easily accessible allylic carbonates and aldehydes without any preactivation. The synergistic catalysis method demonstrated herein adds a new dimension to the area of metal-mediated C allylation.
Keywords: aldehyde umpolung; C allylation; N-heterocyclic carbenes; Palladium; synergistic catalysis

NOx reduction at near ambient temperatures and under lean-burn conditions on modified pd surfaces - Roy, Kanak; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Palladium surfaces that are modified with O atoms in the subsurface broaden the NO reduction temperature regime up to 325 K with O-2-rich NO+H-2+O-2 compositions. Compared to virgin Pd surfaces, up to 150% higher deNO(x) catalytic activity was observed with modified Pd surfaces at the reaction maximum. Molecular beam instrument and ambient-pressure photoelectron spectroscopy were employed to follow the kinetic and surface changes. These results open up a possibility to realize the cold-start reduction of NOx (deNO(x)). DeNO(x) activity reported in the literature with supported Pd catalysts after a simple calcination in air compares well with our present observations. Surface modification is likely to demonstrate a high potential for other catalytic reactions at relatively low temperatures.
Keywords: heterogeneous catalysis; nitrogen; oxygen; Palladium; surface chemistry

Palladium nanoparticles supported on magnesium hydroxide fluorides: a selective catalyst for olefin hydrogenation - Acham, Vaibhav R.; Biradar, Ankush V.; Dongare, Mohan K.; Kemnitz, Erhard; Umbarkar, Shubhangi B. (ChemCatChem, 2014)
A one-pot synthesis of palladium nanoparticles supported on magnesium hydroxide fluoride has been performed with the fluorolytic sol-gel method. The prepared catalysts were characterized by using various physicochemical techniques. The sol-gel method led to high surface area (>135 m(2)g(-1)), mesoporous catalysts (pore volume=0.19-0.23 cm(3)g(-1), pore diameter=3-5 nm) with uniformly dispersed palladium nanoparticles approximately 2 nm in diameter on the surface. The catalysts synthesized by using different concentrations of aqueous hydrofluoric acid exhibited changing surface and acidic properties. Very high dispersion of palladium on magnesium fluoride (47%) was obtained with 1 wt% palladium loading. The catalysts were used for hydrogenation of various olefins in the presence of other organic functionalities at room temperature and atmospheric hydrogen pressure. Various substituted olefins were hydrogenated with almost 100% conversion and selectivity. The catalysts were recycled efficiently over five cycles without appreciable loss in catalytic activity. There was no palladium leaching under the reaction conditions, which was confirmed by inductively coupled plasma atomic emission spectroscopy analysis. Activation of olefin on the catalyst surface could not be observed by in situ FTIR studies, indicating facile activation of hydrogen on the palladium supported on magnesium hydroxide fluoride.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; magnesium fluorides; Palladium

Towards a sustainable and near ambient DeNO(x) under lean burn conditions: a revisit to no reduction on virgin and modified pd(111) surfaces - Roy, Kanak; Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
Catalytic conversion of NO in the presence of H-2 and O-2 has been studied on Pd(111) surfaces, by using a molecular beam instrument with mass spectrometry detection, as a function of temperature and reactants composition. N-2 and H2O are the major products observed, along with NH3 and N2O minor products under all conditions studied. Particular attention has been paid to the influence of O-2 addition toward NO dissociation. Although O-2-rich compositions were found to inhibit the deNO(x) activity of the Pd catalyst, some enhancement in NO reduction to N-2 was also observed up to a certain O-2 content. The reason for this behavior was determined to be the effective consumption of the H-2 in the mixture by the added O-2 and O atoms from NO dissociation. NO was proven to compete favorably against O-2 for the consumption of H-2, especially <= 550 K, to produce N-2 and H2O. Compared with other elementary reaction steps, a slow decay observed with the 2H + 0 -> H2O step under SS beam oscillation conditions demonstrates its contribution to the rate-limiting nature of the overall reaction. Pd(111) surfaces modified with O atoms in the subsurface (Md-Pd(111)) induces steady-state NO reduction at near-ambient temperatures (325 K) and opens up a possibility to achieve room temperature emission control. A 50% increase in the reaction rates was observed at the reaction maximum on Md-Pd(111), as compared with virgin surfaces. Oxygen adsorption is severely limited below 400 K, and effective NO + H-2 reaction occurs on Md-Pd(111) surfaces. Valence band photoemission with a UV light source (He I) under different oxygen pressures with APPES clearly identified the characteristics of the Md-Pd(111) surfaces and PdO. The electron-deficient or cationic nature of Md-Pd(111) surfaces enhances the NO dissociation and inhibits oxygen chemisorption <= 400 K under lean-burn conditions.
Keywords: deNO(x); heterogeneous catalysis; Hydrogen; lean burn; molecular beam; nitric oxide; Palladium; surface modification

Modular synthesis of biaryl-substituted phosphine ligands: application in microwave-assisted palladium-catalyzed C-N cross-coupling reactions - Singh, Chandani; Rathod, Jayant; Jha, Vishwajeet; Panossian, Armen; Kumar, Pradeep; Leroux, Frederic R. (European Journal of Organic Chemistry, 2015)
Biaryl-substituted monophosphine-based ligands have been synthesized by transition-metal-free ARYNE cross-coupling reaction of aryllithiums with 1,2-dibromobenzene and subsequent regioselective functionalization through bromine-lithium interconversion. These ligands were employed in palladium-catalyzed C-N bond-forming reactions. The reaction was found to be general with wide substrate applicability. A wide variety of both primary and secondary amines were successfully coupled with an array of differently substituted halobenzenes under microwave irradiation to give the expected products in good to excellent yields. A number of biaryl-substituted phosphine ligands screened for the coupling reaction showed that steric bulk and the electronic properties of substituents on phosphorus play a crucial role in governing the catalytic activity of C-N cross-coupling reactions.
Keywords: Biaryls; Cross-coupling; Homogeneous catalysis; Microwave chemistry; Palladium; Phosphines; synthetic methods

Palladium supported ionic liquid phase catalyst (Pd@SILP-PS) for room temperature Suzuki-Miyaura cross-coupling reaction - More, S.; Jadhav, S; Salunkhe, R.; Kumbhar, A. (Molecular Catalysis, 2017)
A new Pd-SILP based on amino functionalized imidazolium ionic liquid immobilized on Merrifield resin (Pd@SILP-PS) has been synthesized. The catalyst was characterized by different techniques like FT-IR, SEM-EDS, TEM, TGA-DTA and XPS. The catalyst has shown to be highly active in Suzuki-Miyaura cross-coupling reaction of various aryl halides and aryl boronic acids in ethanol at room temperature. The activity of catalyst and the nature of product were highly dependent on the type of the solvent used, as well as the substituents present on the aryl halides. The protic polar solvent ethanol gave desired cross-coupling product in good to excellent yields at room temperature. However the aprotic polar solvent THF gave homocoupling product. The catalyst showed at least five times recyclability without a decrease in product yield.
Keywords: Immobilization; Ionic liquid; Palladium; SILP; Suzuki-Miyaura reaction

Electrocatalysis of oxygen reduction reaction on shape-controlled pt and pd nanoparticles-importance of surface cleanliness and reconstruction - Devivaraprasad, Ruttala; Nalajala, Naresh; Bera, Bapi; Neergat, Manoj (Frontiers in Chemistry, 2019)
Shape-controlled precious metal nanoparticles have attracted significant research interest in the recent past due to their fundamental and scientific importance. Because of their crystallographic-orientation-dependent properties, these metal nanoparticles have tremendous implications in electrocatalysis. This review aims to discuss the strategies for synthesis of shape-controlled platinum (Pt) and palladium (Pd) nanoparticles and procedures for the surfactant removal, without compromising their surface structural integrity. In particular, the electrocatalysis of oxygen reduction reaction (ORR) on shape-controlled nanoparticles (Pt and Pd) is discussed and the results are analyzed in the context of that reported with single crystal electrodes. Accepted theories on the stability of precious metal nanoparticle surfaces under electrochemical conditions are revisited. Dissolution, reconstruction, and comprehensive views on the factors that contribute to the loss of electrochemically active surface area (ESA) of nanoparticles leading to an inevitable decrease in ORR activity are presented. The contribution of adsorbed electrolyte anions, in-situ generated adsorbates and contaminants toward the ESA reduction are also discussed. Methods for the revival of activity of surfaces contaminated with adsorbed impurities without perturbing the surface structure and its implications to electrocatalysis are reviewed.
Keywords: Adsorption; Dissolution; oxygen reduction reaction; Palladium; platinum; reconstruction; shape-control; surface cleaning

Selective hydrogenolysis of 5-(hydroxymethyl)furfural over Pd/C catalyst to 2,5-dimethylfuran - Solanki, B. S.; Rode, C. V. (Journal of Saudi Chemical Society, 2019)
everal metal supported catalysts were prepared and evaluated for 5-(hydroxymethyl)furfural (5-HMF) hydrogenolysis to 2,5-dimethylfuran (2,5-DMF) which is a renewable potential fuel additive. Among the prepared catalysts, 3%Pd/C showed excellent performance in terms of complete conversion of 5-HMF along with the highest selectivity of 99% to 2,5-DMF. Detailed physico-chemical characterisation was done in order to understand structure-activity correlation. Uniformly dispersed Pd nanoparticles on activated carbon provided the adsorption surface to enhance the hydrogenation of 5-HMF. Reaction was well optimised and established by extensive study of different reaction parameters like temperature, pressure, reaction time, stirring effect, substrate loading and metal loading.
Keywords: Biomass; Fuel additive; heterogeneous catalysis; Hydrogenolysis; Palladium

Palladium-catalyzed insertion of ethylene and 1,1-disubstituted difunctional olefins: an experimental and computational study - Gaikwad, Shahaji R.; Patel, Ketan; Deshmukh, Satej S.; Mote, Nilesh R.; Birajdar, Rajkumar S.; Pandole, Satish P.; Chugh, Jeetender; Chikkali, Samir H. (ChemPlusChem, 2020)
Insertion or coordination copolymerization of ethylene with di-substituted olefins is challenging and the choice of di-substituted mono-functional olefin versus di-substituted di-functional olefin (DDO) appears to be decisive. Here we show that DDO-inserted species are amenable to ethylene insertion and polymerization. DDOs such as 2-acetamidoacrylic acid (AAA), methyl 2-acetamidoacrylate (MAAA), and ethyl 2-cyanoacrylate (ECA) were treated with palladium complex [P perpendicular to OPdMe(L)] (P perpendicular to O=kappa(2)-P,O-Ar2PC6H4SO2O with Ar=2-MeOC6H4; L=C2H6OS) and the existence of respective insertion intermediates in moderate yield (up to 37 %) was established. These intermediates were exposed to ethylene and corresponding ethylene-inserted products were isolated and characterized. A careful comparison with three model compounds confirmed ethylene insertion and polymerization. Thus, the combined experimental and computational investigations show that DDO-inserted species can undergo ethylene insertion and polymerization.
Keywords: Homogeneous catalysis; insertion copolymerization; Olefins; Palladium; Polyethylene

Palladium-catalyzed oxidative annulation of pyrrolylalkyl-1H-azoles: towards the synthesis of polyheterocyclic arenes - Tripathi, Krishna N.; Bansode, Avinash H.; Singh, Ravi P. (Synthesis-Stuttgart, 2020)
A highly efficient and regioselective palladium-catalyzed annulation protocol for a series of linear and terminally substituted 1,2- and 1,3-di(heteroaryl)alkanes to the corresponding polyheterocyclic arenes is reported. Herein, intramolecular oxidative coupling involving double C(sp(2))-H bond functionalization provides a feasible access to biheteroaryl systems annulated to a six-membered ring. The methodology is not restricted to six-membered annulations and was extended to the synthesis of compounds with a seven-membered ring and biheteroaryl core.
Keywords: C-H functionalization; imidazoles; oxidative coupling; Palladium; pyrroles

Highly efficient and reusable polymer supported palladium catalyst for copper free sonogashira reaction in water - Sruthi, Pambingal Rajan; Nimmi, Puthan Purayil; Babu, Sukumaran Santhosh; Anas, Saithalavi (ChemistrySelect, 2022)
Development of a novel, greener and efficient heterogeneous catalytic system for copper free Sonogashira reaction in water is described. This novel catalyst can be easily prepared by a simple method through synthetic modification of nitrile group in Polyacrylonitrile (PAN) using monoethanolamine (MEA) followed by its complexation with palladium chloride (PdCl2). The resulting polymer Pd complex (mPAN-Pd) was characterized by means of Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray Spectroscopy (EDAX), Inductively Coupled Mass Spectrometry (ICP-MS) and X-ray Photo Electron Spectroscopy (XPS) analyses. mPAN-Pd was then explored as highly efficient heterogeneous catalyst for Sonogashira coupling reaction under copper and ligand free conditions in water affording the corresponding coupling products up to 97 % isolated yield. Moreover, the catalyst was recovered by simple filtration after the reaction and reused for next 5 cycles with excellent stability and activity. This is the first report on the use of ethanolamine modified PAN Pd (II) complex as an efficient heterogeneous catalyst for a coupling reaction.
Keywords: catalysis; green chemistry; Palladium; Polymer Support; Sonogashira coupling

Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group

Selective production of C9 monomeric phenols via hydrogenolysis of lignin using Pd-(W/Zr/Mo oxides)-supported on biochar catalyst - Gurrala, Lakshmiprasad; Kumar, M. Midhun; Sharma, Shweta; Paek, Changyub; Vinu, R. (Fuel, 2022)
Valorizing lignin to phenolic monomers and fine chemicals is an essential component of a sustainable biorefinery that uses lignocellulosic feedstocks. In this study, Pd-metal oxides (ZrO2, WOx, MoO3) supported on activated biochar (ABC) catalysts were developed for hydrogenolysis of lignin. The metals (2% Pd, 5% Zr, 5% W, 5% Mo) were supported on activated biochar using the wetness impregnation method, and the catalysts were extensively characterized. The effect of addition of secondary metals on active surface properties such as acidity, Pd metal particle size and dispersion were also evaluated. The selectivity to C9 monomeric phenols followed the trend: 2Pd-5Mo/ABC (57.3%) > 2Pd-5Zr/ABC (49.2%) > 2Pd-5W/ABC (45%) > 2Pd/ABC (42.9%). The maximum C9 phenolic monomer yield achieved in this study was similar to 22 wt%. The fractional conversion of lignin was 67-69% with Pd-metal oxide catalysts. The presence of Mo in the catalyst inhibited the hydrogenation of aliphatic C-alpha = C-beta in lignin and led to the formation of t-isoeugenol, while the presence of W and Zr resulted in selective formation of the hydrogenated product, propyl guaiacol. Using model compounds, it is proved that the formation of propyl guaiacol is via hydrogenation of t-isoeugenol, and not through dehydroxylation of propanol guaiacol. The dehydroxylation activity of the catalysts is attributed to the higher Lewis acidity and electropositive nature of the metals. A notable carbon atom economy of 47-50% towards total phenolic monomers was achieved with 2Pd/ABC, 2Pd-5Mo/ABC and 2Pd-5Zr/ABC catalysts.
Keywords: Activated biochar; Guaiacol; Hydrogenolysis; lignin; Metal oxides; Palladium

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Kinetic investigation on palladium-catalyzed carbonylation of allyl alcohol - Tonde, Sunil S.; Rajurkar, Kalpendra B.; Pagar, Nitin S. (International Journal of Chemical Kinetics, 2025)
Palladium-catalyzed carbonylation of allyl alcohol to 3-butenoic acid has been investigated. A significant effect of halide promoters, p-tolylsulfonic acid (TsOH), water, solvents, and PPh3 concentration activity and selectivity has been studied. Detailed kinetics of this reaction was investigated in a temperature range of 363-383 K. The influence of parameters such as stirring speed, allyl alcohol, catalyst, benzyltriethylammonium chloride (BTEAC), TsOH concentrations, and CO partial pressures on the activity and selectivity has been studied. An empirical rate equation was suggested and found to be fairly consistent with observed rate data. In addition, the activation energy and kinetic parameters were evaluated.
Keywords: allyl alcohol; Carbonylation; halide promoters; kinetics; Mechanism; Palladium

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation